Addressing barriers to evidence-based medicine in pediatric surgery: an introduction to the Canadian Association of Paediatric Surgeons Evidence-Based Resource. Issue 1 (6th January 2022) - Grandpierre, Viviane; Oltean, Irina; Kaur, Manvinder; Nasr, Ahmed
Abstract : Background: Pediatric surgical practice lags behind medicine in presence and use of evidence, primarily due to time constraints of using existing tools that are not specific to pediatric surgery, lack of sufficient patient data and unstructured pediatric surgery training methods. Method: We developed, disseminated and tested the effectiveness of an evidence-based resource for pediatric surgeons and researchers that provides brief, informative summaries of quality-assessed systematic reviews and meta-analyses on conflicting pediatric surgery topics. Results: Responses of 91 actively practicing surgeons who used the resource were analysed. The majority of participants found the resource useful (75%), improved their patient care (66.6%), and more than half (54.2%) found it useful in identifying research gaps. Almost all participants reported that the resource could be used as a teaching tool (93%). Conclusion: Lack of awareness of the resource is the primary barrier to its routine use, leading to potential calls for more active dissemination worldwide. Users of the Canadian Association of Paediatric Surgeons Evidence-Based Resource find that the summaries are useful, identify research gaps, help mitigate multiple barriers to evidence-based medicine, and may improve patient care.